Reduced weekly subcutaneous doses of bortezomib in combination with cyclophosphamide and dexamethasone for newly diagnosed multiple myeloma - Farzaneh Ashrafi; Azadeh Moghaddas; Ali Darakhshandeh (Wolters Kluwer Medknow Publications, 2020)
Objective: A combination of bortezomib, cyclophosphamide, and dexamethasone is highly effective in the treatment of newly diagnosed multiple myeloma. Neuropathy is a dose-limiting adverse effect of this regimen. Subcutaneous and weekly injection instead of biweekly intravenous administration are used to reduce neuropathy. In this study, patients treated with subcutaneous weekly reduced the dose of bortezomib to reduce neuropathy and cost of treatment. Methods: This is an interventional study, including 16 patients. Enrolled patients received bortezomib 1 mg/m2 subcutaneously, cyclophosphamide 300 mg/m2 intravenously, and dexamethasone 40 mg intravenously days 1, 8, 15, and 22 of a 28 cycle. Findings: The overall response rate (≥partial response [PR]) was 93.8%. Thirteen of 16 patients (81.3%) were in an acceptable PR and complete response. Two patients (12.5%) achieving a PR. Meantime to achievement, the best response was 71 (55-87) days. Median progression-free survival was 33 (2-56) months, and autologous stem cell transplantation was performed for 68.8% of patients. Five patients (31.25%) experienced Grade I and one patient (6.25%) Grade III (no Grade 2 or 4) of peripheral neuropathy. Dose reduction and drug discontinuation was required in one patient (6.25%). Conclusion: A reduced subcutaneous, weekly dose of bortezomib in combination with cyclophosphamide and dexamethasone is effective with manageable profile toxicity and acceptable cost.